Cold Water Immersion After a Handball Training Session: The Relationship Between Physical Data and Sensorial Experience - L'Hermette, Maxime; Castres, Ingrid; Coquart, Jeremy; Tabben, Montassar; Ghoul, Nihel; Andrieu, Bernard; Tourny, Claire (Frontiers in Sports and Active Living, 2020)
The aim of this study was to examine the relationship between the physiological data from subjects and their reported sensory experiences during two types of recovery methods following a handball training session. Female handball players (average age: 21.4 ± 1.3 years; weight: 59.2 ± 3.3 kg; height: 158 ± 3 cm; body mass index, 23.4 ± 2.0 kg.m−2) carried out an athletic training session (rating of perceived exertion RPE: 14.70 ± 0.89) with either a passive recovery (PR) period or cold water immersion (CWI) for 14 min) (cross-over design). Physiological data were collected during the recovery period: CWI had a greater effect than PR on heart rate (HR; bpm), the higher frequencies (HF) of heart rate variability (HRV: 46.44 ± 21.50 vs. 24.12 ± 17.62), delayed onset muscle soreness (DOMS: 1.37 ± 0.51 vs. 2.12 ± 1.25), and various reported emotional sensations. Spectrum HRV analysis showed a significant increase in HF during CWI. Sensorial experiences during the recovery periods were gathered from verbatim reports 24 h later. Players' comments about CWI revealed a congruence between the physiological data and sensorial reports. They used words such as: “thermal shock,” “regeneration,” “resourcefulness,” “dynamism,” and “disappearance of pain” to describe their sensations. In conclusion, this study demonstrated the link between physiological and experiential data during CWI and we propose that action of the parasympathetic system on the autonomic nervous system can, at least in part, explain the observed correlations between the corporeal data measured and the sensorial experiences reported.